Morse taper implant macrodesign, loading protocol and site of installation – retrospective study of 5,601 implants - MACHADO,Rafael Coutinho Mello (2019)
Abstract Introduction The long-term implant-supported prosthetic rehabilitation monitoring is extremely important in evaluating parameters that could interfere in the success of the treatment. Objective To evaluate the influence of macrodesign (shape of the body and apex), length and diameter, insertion torque, site of installation as well as the loading protocol, on long-term survival rates. Material and method The data obtained was from the medical records of rehabilitated patients who had had at least one Morse taper implant surgery done at ILAPEO School between 2006 -2012. Incomplete medical records, from which it would have been impossible to extract all data essential to complete the study, were excluded. Result A total of 1,142 patient’s medical records comprised the sample; documenting the progress of 5,601 implants, done in both jaws and mandibles. The final survival rate was 98.31%, over an average time of 37.54 months. The type of implant most used was cylindrical (70.33%). The mean installation torque most evidenced in the study was between 41 and 50 Ncm. A logistical regression analysis showed that none of the following variables, site of installation, body and apex shape designs and length, had any significant statistical influence on implant loss. Torque increase and diameter influenced implant loss while immediate loading favored implant maintenance. Conclusion It can be concluded that Morse taper implants present a long-term survival rate that can be lowered by excessive torque, as well as by the diameter of the implant.